Respuesta :

Answer:

y = 3x - 6

Step-by-step explanation:

What you do is you plug both points in for the equation 2 times and solve as a system of equations.

Equation of a line: y = mx + b

(x,y) = (3,3)

(x,y) = (6,12)

3 = 3m + b

12 = 6m + b

Subtract equations to get rid of b to solve for m.

12 - 3 = 6m - 3m + b - b

9 = 3m

m = 3

Plug m back into both equations get b.

3 = 3(3) + b

b = -6

12 = 6(3) + b

b = -6

y = 3x - 6

Answer:

[tex]\displaystyle y = 3x - 6[/tex]

Step-by-step explanation:

First, find the rate of change of the line:

[tex]\displaystyle \frac{-y_1 + y_2}{-x_1 + x_2} = m \\ \\ \frac{-3 + 12}{-3 + 6} = m \hookrightarrow \frac{9}{3} = m \\ \\ \boxed{3 = m}[/tex]

_______________________________________________

Now plug all the information into the Slope-Intercept Formula. It does not matter which ordered pair is chosen:

[tex]\displaystyle 12 = 3[6] + b \hookrightarrow 12 = 18 + b; -6 = b \\ \\ \boxed{\boxed{y = 3x - 6}} \\ \\ OR \\ \\ 3 = 3[3] + b \hookrightarrow 3 = 9 + b; -6 = b \\ \\ \boxed{\boxed{y = 3x - 6}}[/tex]

I am joyous to assist you at any time.